2020
DOI: 10.1590/1678-4324-2020180513
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Mediated Alleviation of Salinity Stress Regulated by Silicon Transporter Genes (Lsi1 and Lsi2) in Indica Rice

Abstract: Silicon accumulation is known to improve tolerance of plants under both biotic and abiotic stress. Salinity stress is an inevitable crisis causing wide spread damage to rice leading to food insecurity. The influence of Si (1mM) on two rice cultivars cv. Ghanteswari (high accumulator) and cv.Badami (low accumulator) which differs in Si uptake potential under saline (10ds/m EC) and non-saline conditions were studied in nutrient culture. The Si transporter genes were isolated and characterized to determine their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…EL value reflects the extent of membrane damage and cellular integrity, while MDA represents the oxidative burst induced by salinity or any other stresses [ 38 ]. Salinity stress tends to increase cellular injury by enhancing EL [ 13 ]. Our findings demonstrated that salinity stress causes higher EL and MDA, particularly in the salt-sensitive BRRI dhan48, probably due to cellular oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EL value reflects the extent of membrane damage and cellular integrity, while MDA represents the oxidative burst induced by salinity or any other stresses [ 38 ]. Salinity stress tends to increase cellular injury by enhancing EL [ 13 ]. Our findings demonstrated that salinity stress causes higher EL and MDA, particularly in the salt-sensitive BRRI dhan48, probably due to cellular oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Reports revealed that, after Si application in rice, thicker levels of casparian bands both in the exodermis and endodermis were formed, which might play partial roles in restricting Na + from entering the symplastic system or transpiration stream [ 49 , 50 ]. Si supplementation has also been reported to augment the cellular K + content in plants under salinity [ 13 ]. We found that 2 mM Si pre-treatment contributed to prevent the K + loss of shoot in both BRRI dhan48 and Binadhan-10 under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations